IMPLEMENTASI MANAJEMEN PENGEMBANGAN MUTU DOSEN PERGURUAN TINGGI AGAMA ISLAM NEGERI DI PROVINSI ACEH - Husaini Husaini; Jumat Barus (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
This study aims to analyze the implementation and evaluation of quality development of PTAIN lecturers in Aceh. A qualitative research method and descriptive approach is applied in the research. The research result shows that the implementation of quality development of PTAIN lecturers in Aceh is done by referring to the strategic plan or programs prepared at the beginning of the year. The forms of implementation of lecturer quality development include room visits, inspection to lecturers’ learning devices, and providing opportunities for lecturers to increase their competence and professionalism through various exercises and benchmarking to other leading Islamic universities. The evaluation for the lecturers quality development is carried out through routine meetings, weekly, mid semester, and annually at the beginning of academic year. The results of the evaluation will become supplementary materials for the institutions in following up the lecturers’ performance on the lecturers’ daily activities. The development carried out to the lecturers are in the form of admonition, providing training and development to increase the lecturers’ competence and professionalism, and also doing routine religious lectures.